An investigation into farmers’ perceptions and experiences of engaging with continued professional development - Connolly, Roisin (STER, 2024)
The aim of this research was to investigate the perceptions and experiences of farmers when engaging with continued professional development (CPD) in Ireland. The data was collected through a combination of online questionnaires and semi-structured interviews. The main questions seeking to be answered were ‘how farmers interact with CPD’, ‘where farmers access information relating to CPD’ and ‘are the courses currently being run through organisations relevant to the needs of farmers? The purpose was to understand, from the perspective of farmers, the levels of awareness there is relating to CPD, while also investigating how this may impact on levels of interest. The objectives of this research were: 1.To explore the experiences of farmers in relation to accessing professional development and new information relating to farming techniques and equipment. 2. To identify the types of resources used by farmers when accessing training and continued education. 3. To gather the views and opinions of farmers relating to awareness and interest in upskilling and CPD. The importance of continued professional training and development, within the agricultural sector, is recognised and emphasised by the National Skills Strategy 2025 (Teagasc, 2018). It is vital to ensure economic com petitiveness and, in terms of agriculture, is essential to help the wider farming population cope with constant and fast paced changes (LIT & BRC, 2019). It is important to note that, a ‘farmer’ in this research refers to any individual who is involved in the operations of a farm on either a frequent basis or in a casual capacity, this can include family members and those managing accounts or otherwise.
Keywords: CPD; Farming; CPD for Farmers; Lifelong learning; Upskilling